2021
DOI: 10.3390/ijerph18105500
|View full text |Cite
|
Sign up to set email alerts
|

The Mood-Improving Effect of Viewing Images of Nature and Its Neural Substrate

Abstract: It has been recently suggested that contact with nature improves mood via reducing the activity of the prefrontal cortex. However, the specific regions within the prefrontal cortex that underlie this effect remain unclear. In this study, we aimed to identify the specific regions involved in the mood-improving effect of viewing images of nature using a 52-channel functional near-infrared spectroscopy (fNIRS). Specifically, we focused on the orbitofrontal cortex (OFC) and dorsolateral prefrontal cortex (dlPFC), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…Awe may transfer people’s attention from themselves to a bigger picture and increase positive feelings, such as connectedness and humility, which benefit people, especially when facing adverse events [ 14 , 15 ]. Second, coloring that provides a sense of being in nature, such as viewing nature pictures or connecting with the natural environment, can improve mood and reduce anxiety [ 16 , 17 ]. Contact with nature may help people recover from stressful situations and improve attention concentration, subsequently enhancing mental health [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Awe may transfer people’s attention from themselves to a bigger picture and increase positive feelings, such as connectedness and humility, which benefit people, especially when facing adverse events [ 14 , 15 ]. Second, coloring that provides a sense of being in nature, such as viewing nature pictures or connecting with the natural environment, can improve mood and reduce anxiety [ 16 , 17 ]. Contact with nature may help people recover from stressful situations and improve attention concentration, subsequently enhancing mental health [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the specific regions within the prefrontal cortex that respond to the reduction of oxy-Hb in the right frontal lobe due to the green effect have been unclear. Recently, it has been reported that, using functional near-infrared spectroscopy, the oxy-Hb concentration in the right orbitofrontal cortex significantly decreased while viewing images of nature [ 23 ]. The orbitofrontal cortex integrates information from the sensory cortex, autonomic areas of the brainstem, and the amygdala and plays an essential role in value expression and emotional processing [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the memory retrieval (for both experimental and control interventions), subjects' heart rate (HR) and heart rate variability (HRV) were monitored using an Apple Watch Series 4 (Apple Inc.), the accuracy of which has been validated ( 25 , 26 ). Immediately after memory retrieval in each section, subjects indicated their present mood in terms of pleasure, relaxation, and vigor using a visual analog scale ( 27 ). For data analysis of HR, HRV, and mood, the average of the two sessions was used.…”
Section: Methodsmentioning
confidence: 99%